IDENTIFICATION OF STAPHYLOCOCCUS SP. ISOLATES FROM PIG TONSILS BASED ON MANNITOL SALT AGAR TEST - Meigagina Dwi Rahmawati; I Wayan Suardana; Nyoman Sadra Dharmawan (Buletin Veteriner Udayana, 2025)
Bacteria are microorganisms that can cause various diseases in humans and animals, as well as play a significant role in food safety concerns. One of the most frequently encountered bacterial genera is Staphylococcus sp., which naturally exists as normal flora on the skin and mucous membranes of the digestive and respiratory systems. However, under certain conditions, these bacteria can become pathogenic and lead to infections. Additionally, Staphylococcus species are often found in food products such as meat and milk, posing potential public health risks. This study aims to identify Staphylococcus sp. species from isolates stored at the Veterinary Public Health Laboratory, Faculty of Veterinary Medicine, Udayana University. The isolates were obtained from the tonsils of healthy Landrace piglets aged 2–3 months, collected from Sangeh, Selat, and Taman Giri in Badung Regency, Bali Province. The research methodology included isolate cultivation, primary identification tests such as Gram staining and the catalase test, followed by biochemical tests, including the coagulase test and mannitol salt agar (MSA) test. The identification results revealed that out of 40 Staphylococcus sp. isolates examined, 22 isolates were identified as Staphylococcus aureus, 10 isolates as Staphylococcus epidermidis, and 8 isolates as Staphylococcus saprophyticus. These findings indicate that Staphylococcus aureus was the predominant species in the tested samples. Due to its pathogenic potential, continuous surveillance of Staphylococcus in animals and animal-derived products is essential to mitigate the risk of transmission to humans. Implementing stringent hygiene and sanitation measures in the handling and processing of animal products is recommended to minimize bacterial contamination.